Microbial Pathogenesis and Pathophysiology of Alzheimer's Disease: A Systematic Assessment of Microorganisms' Implications in the Neurodegenerative Disease - Ekundayo, Temitope Cyrus; Olasehinde, Tosin Abiola; Okaiyeto, Kunle; Okoh, Anthony I. (Frontiers in Neuroscience, 2021)
Microbial infections have been linked to the pathogenesis and pathophysiology of Alzheimer's disease (AD) and other neurodegenerative diseases. The present study aimed to synthesise and assess global evidence of microbial pathogenesis and pathophysiology in AD (MPP-AD) neurodegeneration conditions using integrated science mapping and content analytics to explore the associated research landscape. Relevant MPP-AD documents were retrieved from Web of Science and Scopus according to PRISMA principles and analysed for productivity/trend linked to authors/countries, thematic conceptual framework, and international collaborative networks. A total of 258 documents published from 136 sources and 39.42 average citations/document were obtained on MPP-AD. The co-authors per document were 7.6, and the collaboration index was 5.71. the annual research outputs increased tremendously in the last six years from 2014 to 2019, accounting for 66% compared with records in the early years from 1982 to 1990 (16%). The USA (n=71, freq.=30.34%), United Kingdom (n=32, freq.=13.68%) and China (n=27, 11.54%) ranked in first 3 positions in term of country’s productivity. Four major international collaboration clusters were found in MPP-AD research. The country collaboration network in MPP-AD was characteristic of sparse interaction and acquaintanceship (density=0.11, diameter = 4). Overall, international collaboration is globally inadequate (centralization statistics: degree (40.5%), closeness (4%), betweenness (23%), and eigenvector (76.7%)) against the robust authors’ collaboration index of 5.71 in MPP-AD research. Furthermore, four conceptual thematic frameworks (CTF) namely, CTF#1, roles of microbial/microbiome infection and dysbiosis in cognitive dysfunctions; CTF#2, bacterial infection specific roles in dementia; CTF#3, the use of yeast as a model system for studying MPP-AD and remediation therapy; and CFT#4, flow cytometry elucidation of amyloid-beta and aggregation in Saccharomyces cerevisiae model. Finally, aetiology-based mechanisms of MPP-AD, namely, gut microbiota, bacterial infection, and viral infection, were comprehensively discussed. This study provides an overview of MPP-AD and serves as a stepping stone for future preparedness in MPP-AD-related research.